2015
DOI: 10.1002/ab.21564
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analytic results of ethnic group differences in peer victimization

Abstract: Research on the prevalence of peer victimization across ethnicities indicates that no one group is consistently at higher risk. In the present two meta-analyses representing 692,548 children and adolescents (age 6-18 years), we examined ethnic group differences in peer victimization at school by including studies with (a) ethnic majority-minority group comparisons (k = 24), and (b) White and Black, Hispanic, Asian, and Aboriginal comparisons (k = 81). Methodological moderating effects (measure type, definition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 187 publications
(117 reference statements)
5
87
1
3
Order By: Relevance
“…It is quite well‐established, for example, that sex can influence both frequency of peer victimization (more often higher in boys) and levels of reported somatic problems (usually higher in girls) . Similarly, peer victimization tends to decrease with increasing age, and both peer victimization and somatic problems may vary as a function of ethnicity and socio‐economic background . Regarding the personal characteristics included as control variables in this study, previous research has found that satisfaction with friends and with school, as well as sense of safety, are all negatively related to victimization by peers; similarly, these variables have been reported to be associated with health problems …”
mentioning
confidence: 75%
“…It is quite well‐established, for example, that sex can influence both frequency of peer victimization (more often higher in boys) and levels of reported somatic problems (usually higher in girls) . Similarly, peer victimization tends to decrease with increasing age, and both peer victimization and somatic problems may vary as a function of ethnicity and socio‐economic background . Regarding the personal characteristics included as control variables in this study, previous research has found that satisfaction with friends and with school, as well as sense of safety, are all negatively related to victimization by peers; similarly, these variables have been reported to be associated with health problems …”
mentioning
confidence: 75%
“…The participants that were retained in the core analysis were more likely to be from a white racial background, had parents with at least a bachelor's degree, and had a household income level at or above the median. Although findings from meta-analytic studies indicate that there are few ethnic (Vitoroulis & Vaillancourt, 2015) or socioeconomic (Tippett & Wolke, 2014) differences in peer victimization, and that body dissatisfaction is more prevalent among individuals, TA B L E 5 Unstandardized direct and indirect effects especially women, from white ethnic backgrounds (Wildes, Emery, & Simons, 2001), overweight and obesity are more prevalent among ethnic minority and low-socioeconomic groups (Wang & Beydoun, 2007). As such, future studies should consider the inclusion of diverse populations.…”
Section: Discussionmentioning
confidence: 99%
“…The authors argued that power relations may be more balanced in ethnically diverse schools with multiple ethnic groups. A recent meta-analysis of Vitoroulis and Vaillancourt (2015) focused on ethnic group differences in peer victimisation and suggested that ethnic minority status alone was not strongly associated with a higher level of peer victimisation. Thus, although ethnic minority status poses a risk for victimisation, its effect seems to depend on the context.…”
Section: Prejudice-related Bullyingmentioning
confidence: 99%